El realismo grotesco como recurso de transgresión y subversión en los cuentos de Jorge Kattán Zablah - de Vallbona, Rima (2004)
By applying the grotesque realism, according to Mikhail Bakhtin's method, this essay reviews several carnivalesque instances observed in Jorge Kattán Zablah's short stories, as follows: 1. the cornical cosmovision; 2. the exaggeration that underlines a topsy-turvy vision of the world; 3. carnivalesque language and freedom; 4. ironic-satirical critique (that never becomes a Menippus satire) of socio-political, economic and religious instances observed in Salvadoran realities, which are found in the rest of the continent; 5. carnivalesque intertextuality as a means to transgress and subvert Ihose realities; 6. scatology and degradation with regenerative powers. The corpus of this essay covers Kattán Zablah's first three books and some stories published in various literary magazines. This methodology has the specific purpose of proving that the humor and irony used by the author in his texts are not a frivolous way to approach the subjects related to Latin America, but to attack El Salvador's various socio-political, economic, and religious problems by amusing the readers.